Targeting PI3K, FGFR, CDK4/6 Signaling Pathways Together With Cytostatics and Radiotherapy in Two Medulloblastoma Cell Lines - Lukoseviciute, Monika; Maier, Henrietta; Poulou-Sidiropoulou, Eleni; Rosendahl, Erika; Holzhauser, Stefan; Dalianis, Tina; Kostopoulou, Ourania N. (Frontiers in Oncology, 2021)
Objectives: Medulloblastoma (MB) is treated with surgery and chemotherapy, with or without irradiation, but unfortunately >20% of the patients are not cured, and treatment comes with serious long-term side effects, so novel treatments are urgently needed. Phosphoinositide 3-kinases (PI3K), fibroblast growth factor receptors (FGFR) and cyclin-D kinases (CDK) play critical roles in cancer, and especially PI3K is crucial in MB, so here targeted therapies against them were explored. Methods: MB cell lines DAOY and UW228-3 were exposed to PI3K (BYL719), FGFR (JNJ-42756493) and CDK4/6 (PD-0332991) inhibitors, as single or combined treatments, and their viability, cell confluence, apoptosis and cytotoxicity were examined. Moreover, the inhibitors were combined with cisplatin, vincristine or irradiation. Results: Single treatments with FGFR, PI3K or CDK4/6 inhibitors decreased viability and proliferation slightly, however when combining two inhibitors, or the inhibitors with irradiation, sensitivity was enhanced and lower doses could be used. A more complex pattern was obtained when combining the inhibitors with cisplatin and vincristine. Conclusions: The data suggest that combination treatments with PI3K, FGFR, and CDK4/6 inhibitors for MB could be beneficial and their use should be pursued further. Likewise, their combination with irradiation gave positive effects, while the addition of cisplatin and vincristine resulted in more complex patterns which need to be investigated further.